356 DIVERTICULECTOMY WITH EXTEND MYOTOMY AND ANTERIOR FUNDOPLICATION AS TREATMENT OF INTRATHORACIC ESOPHAGEAL DIVERTICULUM. CASE REPORT AND REVIEW!. (14th September 2020) - Szachnowicz, S; Lopes, L; Fernandes, F; Edno Tales, B; Sallum, R; Cecconello, I
Abstract: : Diverticula of the thoracic esophagus are uncommon disorders and its most appropriate treatment continues unclear. The majority of these diverticula are results of underlying esophageal motility disorders, but some cases are results of periesophageal inflammation. The patients can be asymptomatic, or present dysphagia, regurgitation, aspirated pneumonia, retrosternal pain and weight loss. The barium esophagogram is considered the best study to show and evaluate these cases. Esophageal manometry allow study the esophageal motility abnormality. Methods: Patients with small and asymptomatic diverticula could not require any treatment. Patients with symptomatic or big diverticula should be submitted a diverticulectomy and often with an esophageal myotomy. However the necessity, the esophageal extension and local of the myotomy are still unclear. We describe a case of a 70 yo woman with a intrathoracic esophageal diverticulum. She presented progressive dysphagia to solids in the last two years, associated to regurgitation, retrosternal pain, nausea and weight loss of 10 kilograms. She has no history of aspirated pneumonia. Results: The upper GI endoscopy showed the diverticulum in middle esophagus (25 cm from superior dental arch) and the size in barium esophagogram was 6, 5 x 4, 8 cm. The high resolution esophageal manometry was normal and the patient had no tuberculosis history. She was submitted a thoracoscopic diverticulectomy with extend myotomy (intrathoracic and abdominal) and Dor's fundoplication. She was able to resume a liquid diet by day 3, after a normal barium esophagogram, and was discharged at the 4 post-operative day. After 9 months the patient remains asymptomatic. Conclusion: In our experience, the diverticulectomy associated with an extend myotomy bring excellent results at the esophageal function, allowing an adequate emptying of the esophagus, avoiding severe complications as mediastinitis or esophageal leakage even in patients without severe motility disorder. References: 1. Altorki N K, Sunagawa M, Skinner D B. Thoracic esophageal diverticula. Why is operation necessary? J Thorac Cardiovasc Surg 1993 Feb; 105(2): 260–4. 2. Rice T W, Baker M E. Midthoracic esophageal diverticula. Semin Thorac Cardiovasc Surg 1999 Oct; 11(4): 352–7.